Zonisamide safety in pregnancy: Data from the UK and Ireland epilepsy and pregnancy register. (October 2021) - McCluskey, G; Kinney, MO; Russell, A; Smithson, WH; Parsons, L; Morrison, PJ; Bromley, R; MacKillop, L; Heath, C; Liggan, B; Murphy, S; Delanty, N; et al.
Highlights: Zonisamide can act as a teratogen in animal models, but the magnitude of any potential teratogenic effect is not well established in human pregnancies. From UK and Ireland zonisamide monotherapy data we have identified a possible signal of teratogenicity which needs to be explored further. Zonisamide has been found to be associated with small for gestational age status in 21% of exposures. Mandatory reporting of outcomes would speed up efforts to determine the level of risk associated with lower frequency prescribed antiepileptic drugs. Abstract: Background: Animal data suggest teratogenic effects with zonisamide use and risk of pregnancy losses. Human data following zonisamide exposure are presently limited, but suggest low risk of malformation with elevated risk of low birth weight. Objective: To calculate the major congenital malformation (MCM) rate of zonisamide in human pregnancy and assess for a signal of any specific malformation pattern and associations with birth weight. Methods and materials: Data were obtained from the UK and Ireland Epilepsy and Pregnancy register (UKIEPR) which is an observational, registration, and follow up study from December 1996 to July 2020. Eligibility criteria were use of zonisamide and to have been referred to the UKIEPR before the outcome of the pregnancy was known. Primary outcome was evidence of MCM. Results: From December 1996 through July 2020 there were 112 cases of first trimester exposure to zonisamide, including 26 monotherapy cases. There were 3 MCM for monotherapy cases (MCM rate 13.0% (95% confidence interval 4.5–32.1)), and 5 MCM for polytherapy cases (MCM rate 6.9% (95% confidence interval 3.0–15.2)). While the median birth weight was on 71st and 44th centile for monotherapy and polytherapy cases respectively, there was a high rate of infants born small for gestational age (21% for both). Conclusion: These data raise concerns about a signal for potential teratogenicity with zonisamide in human pregnancy. Given the low numbers reported, further data will be required to adequately counsel women who use zonisamide in pregnancy.